Standardization of the social mobilization process for rural sanitation: A study applied in the city of Divinópolis, state of Minas Gerais (MG), Brazil (Research, Society and Development, 2026)
It is the State’s duty to ensure adequate water and wastewater treatment in both urban and rural areas; however, this reality is not yet fully achieved. While urban areas benefit from consolidated collective systems, rural regions face challenges such as long distances between households, low population density, and limited financial return for centralized systems, requiring the adoption of individual solutions. Studies indicate that a significant portion of the Brazilian population lacks adequate access to basic sanitation, with more critical conditions in rural areas, highlighting limitations in public policy management. In the municipality of Divinópolis/MG, sanitation is the responsibility of the local government, which delegates urban services to COPASA while remaining responsible for rural areas. This arrangement results in a lack of sewage treatment and limitations in water quality, generating dissatisfaction among residents. This study aims to apply Industrial Engineering principles to structure solutions for this context, proposing the role of a social mobilizer as a link between the community and public authorities. The methodology was based on the analysis of official documents, such as the Municipal Basic Sanitation Plan, relevant legislation, studies on individual treatment technologies, and conversations with residents of the rural community of Buritis. As a result, a Standard Operating Procedure (SOP) and supporting tools were developed to standardize the training of mobilizers, demonstrating that process structuring and clear communication strengthen institutional coordination and enable solutions better suited to local needs.